The role of microenterprises in poverty reduction: a case of the city of Bulawayo - Mnkandla, Pana (My University, 2017)
Poverty is one of the biggest challenges that the global community is struggling with. In attempting to address poverty, there has been a tilt towards a microenterprise approach to social development mostly in the global South. The purpose of the study was to explore the role of microenterprises in poverty alleviation and how microenterprises can be optimised as a strategy for poverty alleviation. The primary aim of the study was to explore ways in which microenterprises are contributing to the reduction of household poverty in Bulawayo, Zimbabwe. This was a qualitative study and a multiple case study design was employed. A semi-structured interview schedule was used during interviews with nine participants who had either gone through entrepreneurship or technical skills training and two key informants were selected based on their expertise in enterprise development. Purposive sampling was used to select the participants and thematic analysis was applied to analyse the collected data from all participants. The major findings of this study were that microenterprises have a pivotal role in ensuring basic sustenance, for example basic needs like rent, food, health care and education. All the participants had received business training, however, there still is a disjuncture between business knowledge and application. Challenges that affected participants in the study included lack of machinery, access to credit and lack of a market for their products as indicated in the findings of the study. The participants expressed that microenterprises are a step towards breaking the poverty cycle. The main findings of this study are that microenterprises as a tool in poverty alleviation manages only to afford people basic sustenance, however, it cannot alone be the panacea for poverty reduction, hence it should be seen amongst other interventions in social development.
A report on a research study presented to the Department of Social Work School of Human and Community Development, Faculty of Humanities University of the Witwatersrand in partial fulfilment of the requirements for the degree Master of Arts in Social Work in the Field of Social Development, March 2017
Keywords: Small business--Zimbabwe--Case studies; Poverty--Zimbabwe; Economic development--Zimbabwe; Zimbabwe--Economic conditions